2010
DOI: 10.1007/s11665-010-9717-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulse Parameters on Weld Quality in Pulsed Gas Metal Arc Welding: A Review

Abstract: The weld quality comprises bead geometry and its microstructure, which influence the mechanical properties of the weld. The coarse-grained weld microstructure, higher heat-affected zone, and lower penetration together with higher reinforcement reduce the weld service life in continuous mode gas metal arc welding (GMAW). Pulsed GMAW (P-GMAW) is an alternative method providing a better way for overcoming these afore mentioned problems. It uses a higher peak current to allow one molten droplet per pulse, and a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 45 publications
0
37
0
2
Order By: Relevance
“…Similar studies on weld metal demonstrated that weld metal grains moved toward heat flow. Fine-grained structure on weld metal is formed by a pulsed current [9,25,26]. Figure 3 shows the weld metal microstructure for specimen 2, which used austenitic weld metal and arc characteristics in GMAW-P, which indirectly influence the weld microstructure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies on weld metal demonstrated that weld metal grains moved toward heat flow. Fine-grained structure on weld metal is formed by a pulsed current [9,25,26]. Figure 3 shows the weld metal microstructure for specimen 2, which used austenitic weld metal and arc characteristics in GMAW-P, which indirectly influence the weld microstructure.…”
Section: Methodsmentioning
confidence: 99%
“…It is a variation of constant current welding which involves cycling of the welding current from a high to a low level at a selected regular frequency [7,8]. This process works by forming one droplet of molten metal at the end of the electrode per pulse [9]. The right amount of current is then added to push that droplet across the arc and into the puddle.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature fluctuation inherent in pulsed welding condition also leads to a continuous change in the weld pool size and shape, which favors the initiation of new grains at the weld center. The new grains have been found to be regularly oriented towards the direction of higher thermal gradient which may yield the shift in preferred growth direction [12,24]. Therefore, the results suggest that the solidification in P-mode is initially directed by the {110} planes of base metal grains adjacent to the fusion boundary and then deviated or shifted because of the high turbulent fluid flow.…”
Section: Effect Of Modes Of Metal Transfer On Grain Growthmentioning
confidence: 99%
“…The temperature fluctuation inherent in pulsed welding also leads to a continuous change in the weld pool size and shape, which favours the growth of new grains at the weld centre. The new grains have been found to be regularly oriented toward the direction of higher thermal gradient which may yield the shift in preferred growth direction 21) and generates fine grain structure. However the grain growth in pulse mode is proportional to the heat input.…”
Section: Evolution Of Weld Metal Microstructurementioning
confidence: 99%